Dental Usage Under Changing Economic Conditions - Manski, Richard J. (2012)
OBJECTIVE: The purpose of this article is to examine the relationship between changes in household finances (wealth and income) and changes in dental utilization at the onset of the recent recession in a population of older Americans. METHODS: Data from the Health and Retirement Study (HRS) were analyzed for U.S. individuals aged 51 years and older during the 2006 and 2008 waves of the HRS. We estimated logistic models of (1) starting and (2) stopping dental use between 2006 and 2008 survey periods as a function of changes in household wealth and income, controlling for other potentially confounding covariates. RESULTS: We found that only when household wealth falls by 50 percent or more were older adults less likely to seek dental care. Changes in household income and other changes in household wealth were not associated with changes in dental utilization among this population. CONCLUSIONS: Older Americans’ dental care utilization appeared to be fairly resilient to changes in household finances; only when wealth fell by 50 percent or more did individuals decrease dental use. This finding might extend to other health care services that are preventive, routine, and relatively inexpensive.